Estimation of mean time on a refuse in radioelectronic equipment exploitation systems - Заліський, М. Ю. (Problems of Informatization and Control, 2011)
Procedures of sequential estimation of parameter of exponential probability distribution are considered and analytical correlations are got for calculation of their characteristics